Eficiência da seleção recorrente para redução da altura de plantas em mamoneira (Ricinus communis L - Oliveira, Inocencio Junior de [UNESP] (2007)
The castor bean (Ricinus communis L.) is high social economic value oil plant and a resource source to Brazil. To attend the increasing necessity of the raw material and the difficulty of production in industrial scale, it is essential the genetic material development in adequate size to facilitate the harvest, with precocious and uniform maturation, purposing the utilization of high technology and becoming possible the oil plant production in higher scale. The objective of this work was to evaluate the recurrent selection efficiency for height s reduction of the castor bean plants Guarani cultivar, adequating its size to facilitate the harvest. Were developed four cycles of recurrent selection through the utilization of self-pollinated progenies in the Guarani cultivar for height s reduction of plants, in edaphclimatic condictions of the São Manuel-SP and Botucatu-SP cities. The evaluations of plant s height and grain s productivity (kg.ha-1) of the four selection cycles and of the original cycle (cycle 0) were realized at São Manuel-SP and Botucatu-SP cities, under a casualised blocks design with five repetitions and useful parcels of 30 m2. The variance s analysis for the characteristics plant s height and grain s productivity was made apart to each place and together for the two places and, afterwards it was realized the comparison of the averages by the Tukey test using 5% of probability. Were estimated for the two places, by the regression s analysis... (Complete abstract click electronic access below)